Investigating the effect of the ultra-high absorbent polymer on the sealing property of concrete. Issue 1 (1st January 2019) - Al-Nasra, Moayyad
Abstract: Researcher studied the effect of adding several admixtures to the concrete mix for the purpose of changing and controlling the properties of the final concrete product including the concrete strength, water tightness, concrete sealing capability, and concrete quality. In this study, ultra-high absorbent polymer (UHAP) is added to the concrete mix in order to study its effect on the sealing property of concrete. Other concrete properties will also be studied including the concrete strength and the water tightness. The UHAP has the capability to absorb up to 800 times its weight converting the polymer to a gel of water content that might reach 99%. The volume of the gel increases substantially. This property of the UHAP is utilized in this study. The superabsorbent polymer can absorb water up to 500 times its own weight. The increase in volume of the UHAP inside the concrete mass helps in sealing the concrete cracks and blocking the water flow through the concrete. Cylindrical core is drilled through the concrete cubes to study the sealing property of concrete mixed with UHAP. The cylindrical hole in the concrete cubes is filled with water subjected to high pressure reaching up to 400 kPa.